2018
DOI: 10.26681/jote.2018.020301
|View full text |Cite
|
Sign up to set email alerts
|

Admission Requirements and Practices in Entry-Level Occupational Therapy Programs

Abstract: When establishing admission processes for entry-level doctoral programs, admission requirements for masterlevel programs provide a comparison for consideration. The purpose of this study was to provide information about admission practices for graduate-level occupational therapy programs. The three aims included: 1) to describe admission requirements of a sample of entry-level master's programs; 2) to examine the relationship between attrition and admission requirements for the sample; and 3) to provide a summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…A review of the literature demonstrated a general consensus that both cognitive and non-cognitive qualities and skills of those entering the healthcare professions, including OT, should be assessed at selection (Salvatori, 2001). Evidence to support pre-academic qualifications as a cognitive assessment of graduation success is stronger for those students entering OT training with a previous degree (Bowyer et al, 2018;Katz & Mosey, 1980;Kirchner & Holm, 1997;Kirchner et al, 2001;Lysaght et al, 2009;Shanahan, 2004) as opposed to those from a high-school background (Howard & Jerosch-Herold, 2000;Howard & Watson, 1998;Posthuma & Noh, 1990;Posthuma & Sommerfreund, 1985), with results from this study adding further evidence in support of this.…”
Section: Implications For Occupational Therapy Educationsupporting
confidence: 50%
See 4 more Smart Citations
“…A review of the literature demonstrated a general consensus that both cognitive and non-cognitive qualities and skills of those entering the healthcare professions, including OT, should be assessed at selection (Salvatori, 2001). Evidence to support pre-academic qualifications as a cognitive assessment of graduation success is stronger for those students entering OT training with a previous degree (Bowyer et al, 2018;Katz & Mosey, 1980;Kirchner & Holm, 1997;Kirchner et al, 2001;Lysaght et al, 2009;Shanahan, 2004) as opposed to those from a high-school background (Howard & Jerosch-Herold, 2000;Howard & Watson, 1998;Posthuma & Noh, 1990;Posthuma & Sommerfreund, 1985), with results from this study adding further evidence in support of this.…”
Section: Implications For Occupational Therapy Educationsupporting
confidence: 50%
“…As OT education in the USA made the transition from baccalaureate to master's entrylevel programs, significant positive correlations between P-GPA and/ or GRE scores and GPA in OT courses (OT-GPA) were found across several sites for cohorts ranging from 45-129 (Katz & Mosey, 1980;Kirchner & Holm, 1997;Kirchner et al, 2001;Lysaght et al, 2009). A further contemporary review of academic admissions requirements across American Occupational Therapy Association (AOTA) accredited programs revealed the majority of responding programs require evidence of minimum P-GPA scores (master's, 99.4%, n=155; doctoral, 100%, n=16) and submission of at least one GRE score (master's, 53.9%, n=84; doctoral, 68.8%, n=11), thus contributing to the weight of argument to support the use of the GPA and GRE as predictive tools of academic success (Bowyer et al, 2018).…”
Section: Usa and Canadamentioning
confidence: 99%
See 3 more Smart Citations